2019
DOI: 10.17268/sci.agropecu.2019.02.14
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining a complementary DNA encoding a fructan 1-exohydrolase in yacón, Smallanthus sonchifolius (Poepp. & Endl.) H. Robinson

Abstract: Obtención de un ADN complementario que codifica una fructano 1-exohidrolasa en yacón, Smallanthus sonchifolius (Poepp. &Endl.) H. Robinson Obtaining a complementary DNA encoding a fructan 1-exohydrolase in yacón, Smallanthus sonchifolius (Poepp. & Endl.) H. Robinson

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…These concentrations are below the environmental quality standards of soils in Peru (70 mg/kg) [102]. In the northern Andes of Peru, studies of heavy metals in soils of the Moche River basin have shown variability in their concentrations within the range of what is permitted except in the case of Cu, for which values widely exceed the permitted values [103].…”
Section: Impacts and Risks Linked With The Soil-instability And Accum...mentioning
confidence: 84%
“…These concentrations are below the environmental quality standards of soils in Peru (70 mg/kg) [102]. In the northern Andes of Peru, studies of heavy metals in soils of the Moche River basin have shown variability in their concentrations within the range of what is permitted except in the case of Cu, for which values widely exceed the permitted values [103].…”
Section: Impacts and Risks Linked With The Soil-instability And Accum...mentioning
confidence: 84%